The development of ethnic theory in social sciences - Fukumoto, Mary (1985)
Undoubtedly, anyone who has attempted to study theory about ethnic groups has experienced the confusion that arises from their contradictory postulates. Experts in the field participate in debates about the nature and functions of ethnic groups that rarely reach satisfactory conclusions. Controversies about the flexibility or rigidity of its borders, the presumed subordination characteristic of ethnic aggregates, and the ascribed or acquired nature of its features are commonplace in the literature on ethnic groups in the social sciences. This article presents the development of the theory on ethnic groups over time, since this development offers elements of judgment that help to clarify the discussions (and confusions) in the mentioned subject. I will focus primarily on the discussion of ethnicity between anthropologists and sociologists in North America which has had an undeniable influence at the international level.